Implementasi KMA 183 dalam Pembelajaran Bahasa Arab di MAN 1 Kotamobagu - Fauzia , Syifa; Yasin, Zohra; Nur Iman, Muhammad (Yayasan Daarul Qimmah Gorontalo, 2022)
This article discusses the Implementation of KMA 183 in Arabic Language Learning. The formulation in the study is how the implementation of learning in KMA 183 in MAN 1 Kotamobagu, How to plan and implement Arabic language learning in KMA 183 in MAN 1 Kotamobagu, How to evaluate Arabic learning in KMA 183 in MAN 1 Kotamobagu. The purpose of this study is to find out about the change from KMA 165 to KMA 183. This type of research is qualitative descriptive research with local man 1 kotamobagu research. The data collection methods used are observation, interviews, and documentation. Meanwhile, technical data analysis is carried out through three stages, namely data reduction, display data, and verification. The results of the study are (1) the implementation of KMA 183 on Arabic language learning in MAN 1 Kotamobagu has been good in implementing KMA 183. (2) The planning process, namely preparing administration in the form of syllabus, prota, and prosem is in accordance with KMA 183 and the implementation of learning, namely teachers follow planning, methods, audio-visual media in Arabic language learning (3) Evaluation of learning, namely the existence of mgmp (Subject Teacher Deliberation) activities so that teachers play a role in strategies to improve and strengthen teacher competencies starting discussions and training.